VMware vSphere 6.5 cookbook : over 140 task-oriented recipes to install, configure, and manage, and orchestrate various VMware vSphere 6.5 components /: over 140 task-oriented recipes to install, configure, and manage, and orchestrate various VMware vSphere 6.5 components. (2018) - G. B., Abhilash; Rajendran, Cedric
No abstract available